HERANÇA DA RESISTÊNCIA DE MILHO À ANTRACNOSE FOLIAR - Prochno, Hellen Christine (2013)
The objectives of this study were to measure the resistance/susceptibility of the sixteen maize inbred lines to anthracnose leaf blight (Colletotrichum graminicola (Ces.) G. W. Wils.) and estimate the genetic parameters associated with resistance, as well as study the inheritance of resistance and the genic action involved in the generations descended from crosses between maize inbred lines (Zea mays L.). Firstly, sixteen maize lines were screened for resistance/susceptibility to anthracnose leaf blight in three trials conducted in a randomized block design, with four replications. The plants inoculations were performed when the plants were six to seven completely expanded leaves in two times, the second made seven days after the first inoculation. To quantify the disease severity, six evaluations were performed at weekly intervals, initiated after the first symptoms appear, by use a note scale with amplitude from 1 to 6. Were used the data obtained in the second, fourth and sixth evaluation and data of the area under the disease progress curve (AUDPC) to perform analyzes and estimates of genetic parameters. To study the inheritance of resistance in maize to anthracnose leaf blight, were estimated the genetic parameters of six families derived from crosses between resistant and susceptible lines to C. graminicola. Each family consisted of six generations (P1, P2, F1, F2, RC1 e RC2), which were evaluated for resistance in two trials implanted in a randomized block design in a split-plot, where in the plots were studied the families effects and in splits the generations effects, with three replications. Were used the data estimated in second, fourth and sixth evaluation for the performed the statistical and genetic analysis. The results showed the existence of genetic variability for resistance/susceptibility to anthracnose leaf blight in all inbred lines studied. The inbred lines L 04-2, L 23-1, L 87-3, L 99-4 e L 118-4 stood out for keep the resistance pattern, showing the lowest values of AUDPC in the three trials, were considered important source of resistance to C. graminicola. The estimates genetic parameters indicated low participation of environmental effects on the resistance/susceptibility expression to anthracnose leaf blight and showed the possibility of genetic gains with the artificial selection. The results indicated predominance of additive effects in the inheritance of maize resistance to anthracnose leaf blight in the six families analyzed, explaining up to 99,39% of the phenotypic variation. The high heritability coefficients (broad and narrow sense) observed indicated ease in the artificial selection process by breeding programs. The heterosis estimates were high and negatives in all families studied, revealing the ability of resistant inbred lines (LR 04-2 e LR 23-1) in transmitting the resistance genes for generations affiliated, resulting in lower disease severity. The results showed that the inheritance of maize resistance to anthracnose leaf blight is oligogenic. Predominance of additive genic action, associated with high heritability estimates and oligogenic genetic control, assuming that genetic gains with artificial selection will reach success in the breeding programs that search develop resistant maize populations to anthracnose leaf blight.